Analysis of the profile of patients presenting with sexual assault at Leratong hospital crisic centre,Krugersdorp,South Africa in 2014 - Olayiwola, Akintunde (My University, 2019)
Background: The global prevalence of rape in women is 7.2%, and in Sub Saharan Africa 21%. In South Africa, rape or sexual assault (a form of inter-personal violence) is defined as a person committing an unlawful, intentional act of sexual penetration without the consent of the complainant. Sexual assault damages the physical, sexual, emotional, mental and social wellbeing of individuals and families. Hence it is a big public health hazard. Aim: To explore the characteristics of patients who presented for sexual assault counselling in Leratong Hospital, Krugersdorp, Gauteng, South Africa, from January to December 2014. Methodology: A retrospective, cross-sectional study was undertaken by reviewing the files of 501 patients who fulfilled the inclusion criteria. All the files of the patients who presented to a secondary level hospital in Krugersdorp, South Africa from January to December 2014 were collected and analysed. Results: The mean age of the sexual assault patients was 21.5 years. The majority of participants were black (92.4%), female (96%), single (95.4%), unemployed (83.8%), and Tswana-speaking (42.3%), who had a school education (27.6%) and lived in Mogale city (51.7%). Fifty eight percent of the participants reported that sexual assault had taken place between a Friday and a Sunday, between 18.00 to 05.59 hours. Participants older than 20 years were three times more susceptible to sexual assault at night (p = 0.00). Young participants were sexually assaulted more frequently at the perpetrator’s place (p = 0.01), and at party venues or in cars (p = 0.01). Chi2 and logistic regression analysis were used to determine the association between the patients’ socio-demographic factors and sexual assault characteristics. Conclusion and recommendation: Health workers should play a leading role and coordinate inter-sectorial initiatives involving the department of education and public safety in educating the identified vulnerable groups. Safety and security officials especially the police should consider the identified risk factors for sexual assault and effect targeted interventions.
Research report submitted to the Faculty of Health Sciences at the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master in Family Medicine January 2019